Local History, Transnational Memory in the Romanian Holocaust
XI, 275 p. 13 illus.
Keywords: This book explores the memory of the Romanian Holocaust in Romanian, German, Israeli, and French cultural representations. The essays in this volume discuss first-hand testimonial accounts, letters, journals, drawings, literary texts and films by Elie Wiesel, Paul Celan, Aharon Appelfeld Norman Manea, Radu Mihaileanu, among others.